2023
DOI: 10.2460/javma.23.01.0001
|View full text |Cite
|
Sign up to set email alerts
|

Topical therapy for canine pyoderma: what is new?

Abstract: Antimicrobial-resistant cutaneous infections are increasing in veterinary medicine. The use of systemic antibiotics should be limited to severe cases of pyoderma to decrease the microbial pressure and selection for multidrug-resistant bacteria. Topical antimicrobials with a low-resistance profile, such as chlorhexidine, benzoyl peroxide, and ethyl lactate have been used for decades in veterinary dermatology. However, new alternatives have been explored in the past decade. The goal of this review is to summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The MDR-S antibiogram showed that some isolates were susceptible to amikacin, which has serious side effects, including nephrotoxicity, and requires close monitoring for kidney function [ 47 ]. Therefore, topical therapy is the only option for skin infection with MDR-SP, MRSP, and other MDR MRs [ 16 , 48 , 49 ]. Notably, among the tier 1 antibiotics for typical SP, the β-lactam antibiotics had a very high susceptibility, greater than but potentiated sulphonamides was at 70%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MDR-S antibiogram showed that some isolates were susceptible to amikacin, which has serious side effects, including nephrotoxicity, and requires close monitoring for kidney function [ 47 ]. Therefore, topical therapy is the only option for skin infection with MDR-SP, MRSP, and other MDR MRs [ 16 , 48 , 49 ]. Notably, among the tier 1 antibiotics for typical SP, the β-lactam antibiotics had a very high susceptibility, greater than but potentiated sulphonamides was at 70%.…”
Section: Discussionmentioning
confidence: 99%
“…The MDR-S antibiogram showed that some isolates were susceptible to amikacin, which has serious side effects, including nephrotoxicity, and requires close monitoring for kidney function [47]. Therefore, topical therapy is the only option for skin infection with MDR-SP, MRSP, and other MDR MRs [16,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…SBF, as part of bacterial pyoderma, is more common in dogs than other mammalian species and this fact has stimulated the research on this topic. Treating SBF usually requires a multimodal approach (19). Proper identification and treatment of the primary cause is mandatory since if only symptomatic medications are given, incomplete healing or recurrence is likely to occur (19).…”
Section: Discussionmentioning
confidence: 99%
“…Treating SBF usually requires a multimodal approach (19). Proper identification and treatment of the primary cause is mandatory since if only symptomatic medications are given, incomplete healing or recurrence is likely to occur (19). Systemic antimicrobial drugs (AMD) are routinely used for the treatment of SBF (20).…”
Section: Discussionmentioning
confidence: 99%
“…As our awareness of resistance as a result of antibiotic pressure increases, it is good practice to treat superficial bacterial infections topically as much as possible rather than systemically. Dr. Santoro 16 provides us with an update on topical therapy for canine pyoderma and how we can select the best option for our patients.…”
Section: One Healthmentioning
confidence: 99%